1993
DOI: 10.1111/j.1365-2885.1993.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal distribution of albendazole metabolites following netobimin administration to cattle: relationship with plasma disposition kinetics

Abstract: The gastrointestinal (GI) distribution and plasma disposition kinetics of albendazole (ABZ) metabolites after oral administration of netobimin (NTB) to cattle were studied. Eight Holstein steers (150-180 kg) were surgically fitted with permanent cannulae in the rumen, abomasum and ileum. After post-surgical recovery, the animals were treated orally with a suspension of netobimin zwitterion (400 mg/ml) at 20 mg/kg. Jugular blood and ruminal, abomasal and ileal fluid samples were taken serially over a 96 h perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…Both metabolites are reversibly exchanged between plasma and the GI tract in a pH gradient-mediated distribution process (21). This pH gradient facilitates the concentration of ABZSO in all GI compartments including the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Both metabolites are reversibly exchanged between plasma and the GI tract in a pH gradient-mediated distribution process (21). This pH gradient facilitates the concentration of ABZSO in all GI compartments including the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that plasma concentration profiles of anthelmintic compounds reflect the pattern of exposure of worms in the digestive tract as well as in other tissues [17,18]. BZD anthelmintics are reversibly exchanged between plasma and Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…BZD anthelmintics are reversibly exchanged between plasma and Figure 4. Evolution of the RBZ enantiomeric proportions after iv (left) and sc (right) administration of a racemic dose (7.5 mg/kg) of RBZ to cattle gastrointestinal tract in a pH gradient-mediated distribution process [17]. RBZ is a weak base (pK a 7.8); at plasma pH there will be a higher proportion of this molecule in the lipophilic nonionic form, which facilitates its passive diffusion from plasma to different tissues including the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unsatisfactory ABZ dissolution rate limits its absorption; therefore, it is poorly and erratically absorbed from the gastrointestinal tract. In vivo studies (17,18) have demonstrated that the oral absorption of benzimidazole compounds depends on their dissolution at low pH and is closely related to the rate of gastric emptying and gut transit time. The USP indicates that the dissolution medium used to evaluate ABZ dissolution is 0.1 N HCl (19).…”
mentioning
confidence: 99%